Extraction of perlilla sticks (Symphoricarpos microphyllus H.B.K.) from the Nevado de Toluca Park - Anastacio Martínez, Nancy Diana; Valtierra Pacheco, Esteban; Nava Bernal, Gabino; Franco Maass, Sergio (Instituto de Ecología, A.C., 2016)
This research describes the social process of extraction and commercialization of the perlilla sticks (Symphoricarpos microphyllus H.B.K.) in three communities of the Protected Wildlife Area of the Nevado of Toluca. This research was done through the participant observation, semi-structured interviews, transects and sampling of areas of extraction. The results show that the social agent who generates the demand of this resource is the Government of the Federal District to make rustic brooms used for public cleaning. The social organization around resource extraction is dominated by outside brokers and therefore they obtain most of the economic benefits the perlilla´s extraction. They take advantage of their family and friend relationships with the leaders of cutters. The field work that identifies that the extraction of perlilla has been intensified that some areas already show problems of regeneration of this species that are linked to inadequate cutting technics. This situation could be causing severe ecological, economic and social problems in this natural protected area.